(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to assess the nasal and olfactory functions of patients with chronic obstructive pulmonary disease (COPD).Material and Methods: This prospective study included patients followed-up with COPD in the pulmonary diseases clinic. Patients with COPD without any nasal disease or systemic disease were included in the study. After routine ear nose throat examination was performed, patients with no nasal pathology had the saccharin test and Sniffin’ Sticks tests applied. The control group consisted of volunteers that were living in the same region. The same tests applied to the control group too and the results were compared.Results: There were no significant differences between patient group and control group in terms of categorical variables such as gender, age, smoking status, living area... It was found that the odor functions of COPD patients were significantly affected when compared with the control group. Odor test results were significantly lower in the patient group (p: 0.0001). In addition, mucociliary function was decreased in COPD patients.Conclusions: It was found that the smell and mucociliary functions of COPD patients were worse than the individuals of the same age and this situation had a significant effect on the quality of life of the patients.Keywords: Rhinology; olfactory function; sniffin sticks; mucociliary function; COPD.